A study on renal stone about factors influencing its formation clinical scenario and urinary findings among adults aged 21-60 years in Saurashtra region - Shah, Pankti; Patel, Arpan (International Journal of Research in Medical Sciences, 2020)
Background: Saurashtra is claimed to be ‘stone belt’, even though there is paucity of epidemiological work on this issue; keeping in mind about this problem that ails most parts of the Saurashtra region, which is correctable and preventable, this study was undertaken. Methods: Radiologically diagnosed 100 patients with renal stone were enrolled and interviewed through a proforma approved by institutional ethical committee to study risk factors, clinical scenario, and urinary findings. Urine samples were collected from all the participants of the study and analyzed for the presence of crystals, red blood cells, pus cells as well as urine pH. Data was analyzed with help of EpiInfo™ 7 (CDC Atlanta). Results: Prevalence of renal stone was higher in males (72%); common in age group of 21-35 years. Common findings were recurrent flank pain (81%), gross hematuria (59 %) and renal colic (51%). Familial history (p<0.004), improper water drinking habit (p<0.002), lack of diet modification (p<0.001) according to stone type and stone analysis were found probable causes for the recurrence of stone. Calcium oxalate (75%) stone being the commonest followed by calcium phosphate (15%) and uric acid (7%). Conclusions: Results from this study can be applied in the clinical setting with the goal of reducing the likelihood of stone formation. Preventive measures such as change in diet, drinking behavior when properly addressed can ameliorate the situation in many patients with kidney stone. There is a great scope and role in finding crystals in urine with patients of kidney stone such as checking their compliance, guiding dietary therapy when stone analysis in not available, setting up an screening criteria and diagnosis of renal stone in remote settings where radio-logical investigations are not available.